Heat and Wear Generation for Rolling Contacts - Sextro, Walter (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Development and Experimental Validation of a Point Contact Model for Dynamical Problems with Friction - Sextro, Walter (ASME Design Engineering Technical Conferences)

Localization in Nonlinear Mistuned Systems with Cyclic Symmetry - Sextro, Walter; Popp, Karl; Krzyzynski, Tomasz (Nonlinear Dynamics)
In forced systems with cyclic symmetry localization can occur due toparameter uncertainties. Often, Monte-Carlo simulations are used to findregions, where the system response is sensitive to parameteruncertainties. These simulations require a large computation time.Therefore, an approximate method to calculate the envelopes of thefrequency response functions is developed in this paper. An example of anonlinear system with cyclic symmetry is a bladed disk assembly withfriction dampers. Friction dampers can be installed underneath the bladeplatforms of turbine blades. Due to dry friction and the relative motionbetween blades and dampers, energy is dissipated, which results in areduction of blade vibration amplitudes. By optimizing the mass of thefriction dampers, the best damping effects are obtained, which lead toan increase in the reliability of the turbine. In this paper, thecalculated response of a mistuned bladed disk assembly with frictiondampers is discussed. An approximate method is developed to calculatethe envelopes of the corresponding frequency response function forstatistically varying eigenfrequencies of the blades. Regions wherelocalization can occur with a high probability, are calculated by thismethod.
Keywords: bladed disk assembly; mistuning; sensitivity; localization

Piezoelektrische lineare Schwingungsantriebe - Wallaschek, Jörg; Hemsel, Tobias (Special Antriebstechnik)

Analysing capacity improvements in wireless networks by relaying - Karl, Holger; Mengesha, Seble (Proc. of IEEE Intl. Conf. on Wireless LANs and Home Networks)

Relative jitter packet scheduling for differentiated services - Quynh, T; Karl, Holger; Wolisz, Adam; Rebensburg, Klaus (Proc. 9th IFIP Conf. Perf. Modeling and Eval. of ATM & IP Networks)

The promise of workplace training for non-college-bound youth: Theory and evidence from German apprenticeship - Clark, Damon; Fahr, Rene (CEP Discussion Paper No. 528)

Komponentenorientierte Softwareentwicklung in Softwareunternehmen: Konzeption eines Vorgehensmodells zur Einführung und Etablierung - Schryen, Guido

British Political Speeches from Churchill to Blair

The randomized z-buffer algorithm - Wand, Michael; Fischer, Matthias; Peter, Ingmar; Meyer auf der Heide, Friedhelm; Straßer, Wolfgang (Proceedings of the 28th annual conference on Computer graphics and interactive techniques - SIGGRAPH '01)
We present a new output-sensitive rendering algorithm, the randomized z-buffer algorithm. It renders an image of an arbitrary three-dimensional scene consisting of triangular primitives by reconstruction from a dynamically chosen set of random surface sample points. This approach is independent of mesh connectivity and topology. The resulting rendering time grows only logarithmically with the numbers of triangles in the scene. We were able to render walkthroughs of scenes of up to 10^14 triangles at interactive frame rates. Automatic identification of low detail scene components ensures that the rendering speed of the randomized z-buffer cannot drop below that of conventional z-buffer rendering. Experimental and analytical evidence is given that the image quality is comparable to that of common approaches like z-buffer rendering. The precomputed data structures employed by the randomized z-buffer allow for interactive dynamic updates of the scene. Their memory requirements grow only linearly with the number of triangles and allow for a scene graph based instantiation scheme to further reduce memory consumption.

Data Management in Networks - Meyer auf der Heide, Friedhelm (Graph-Theoretic Concepts in Computer Science)

Parallel Bridging Models and Their Impact on Algorithm Design - Meyer auf der Heide, Friedhelm; Wanka, Rolf (Computational Science - ICCS 2001)

The Algorithms Behind GAIO — Set Oriented Numerical Methods for Dynamical Systems - Dellnitz, Michael; Froyland, Gary; Junge, Oliver (Ergodic Theory, Analysis, and Efficient Simulation of Dynamical Systems)

Extracting Dynamical Behavior via Markov Models - Froyland, Gary (Nonlinear Dynamics and Statistics)

Rigorous computation of topological entropy with respect to a finite partition - Froyland, Gary; Junge, Oliver; Ochs, Gunter (Physica D: Nonlinear Phenomena)

An adaptive subdivision technique for the approximation of attractors and invariant measures: proof of convergence - Junge, Oliver (Dynamical Systems)

Algorithms — ESA 2001, 9th Annual European Symposium Århus, Denmark

Glimpses into the Future of Computer Science Education - Domik, Gitta (J. (UCS))

The numerical detection of connecting orbits - Dellnitz, Michael; Junge, Oliver; Thiere, Bianca (Discrete & Continuous Dynamical Systems - B)

Object-oriented domain specific compilers for programming FPGAs - Mencer, Oskar; Platzner, Marco; Morf, Martin; J. Flynn, Michael (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

Implementation of a Rake Receiver Architecture into a Galileo Receiver - Bischoff, R.; Haeb-Umbach, Reinhold; Schulz, W.; Heinrichs, G. (1st ESA Workshop on Satellite Navigation User Equipment Technology (Navitec 2001))

Automatic generation of phonetic regression class trees for MLLR adaptation - Haeb-Umbach, Reinhold (IEEE Transactions on Speech and Audio Processing)
In this paper, it is shown that a correlation criterion is the appropriate criterion for bottom-up clustering to obtain broad phonetic class regression trees for maximum likelihood linear regression (MLLR)-based speaker adaptation. The correlation structure among speech units is estimated on the speaker-independent training data. In adaptation experiments the tree outperformed a regression tree obtained from clustering according to closeness in acoustic space and achieved results comparable with those of a manually designed broad phonetic class tree
Keywords: acoustic space; adaptation experiments; automatic generation; bottom-up clustering; broad phonetic class regression trees; correlation criterion; correlation methods; maximum likelihood estimation; maximum likelihood linear regression based speaker adaptation; MLLR adaptation; pattern clustering; phonetic regression class trees; speaker-independent training data; speech recognition; speech units; statistical analysis; trees (mathematics)

Multiclass linear dimension reduction by weighted pairwise Fisher criteria - Loog, M.; Duin, R.P.W.; Haeb-Umbach, Reinhold (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We derive a class of computationally inexpensive linear dimension reduction criteria by introducing a weighted variant of the well-known K-class Fisher criterion associated with linear discriminant analysis (LDA). It can be seen that LDA weights contributions of individual class pairs according to the Euclidean distance of the respective class means. We generalize upon LDA by introducing a different weighting function
Keywords: approximate pairwise accuracy; Bayes error; Bayes methods; error statistics; Euclidean distance; Fisher criterion; linear dimension reduction; linear discriminant analysis; pattern classification; statistical analysis; statistical pattern classification; weighting function

Experience-based decision making and learning from examples - Hüllermeier, Eyke (In Proceedings SOR-01 Symposium on Operations Research, Duisburg, Germany)

Ultraschallgeschwindigkeitsmessung zum Bioprozessmonitoring - Cha, Y. L.; Hitzmann, Bernd; Bellgardt, Karl-Heinz; Daur, Peter-Christoph; Henning, Bernd
In diesem Beitrag werden Messungen und Auswertungen der Ultraschallgeschwindigkeitsmessung zur Überwachung von Hefekultivierungen vorgestellt. Die Ultraschallgeschwindigkeit ist abhängig von Biomasse-, Glukose- und Ethanolkonzentration, aber auch von anderen Bioprozessvariablen. Um den Einfluss von Blasen auf das Signal zu reduzieren, wurde der Ultraschallsensor in einem Bypass-System eingesetzt. Es wurden Messungen sowohl im Flow- als auch Stop-Flow-Betrieb durchgeführt. Um die richtigen Informationen aus diesem unspezifischen Signal zu erhalten, wurde ein multilineares Regressionsmodell berechnet, wobei die Biomasse-, Glukose- und Ethanolkonzentration als unabhängige Variablen dienten. Ein Beispiel der Ergebnisse ist in Abbildung eins gezeigt. Es sind die Biomasse-, Glukose- und Ethanolkonzentration während einer Saccharomyces cerevisiae Kultivierung dargestellt. Die Parameter des multilinearen Regressionsmodells wurden durch Verwendung der Daten aus der dargestellten Kultivierung identifiziert. Wird dieses Modell zur Auswertung auf die Signale anderer Prozesse übertragen, ist das Ergebnis ähnlich, jedoch vergrößert sich der Fehler der Schätzung. Die Ergebnisse sowie Erfahrungen werden ausführlich in dem Beitrag diskutiert.

Quality inspection and characterisation of ultrasonic sensor properties using a PC-controlled scanning measuring system - Henning, Bernd; Prange, Stefan; Dierks, Karsten; Daur, Peter-Christoph
Nowadays the use of ultrasonic sensors for process control for flow, level or concentration measurement is wide spread. In this application there are high demands for a defined and stable quality of the properties of such ultrasonic sensors. For the detailed investigation and characterization of ultrasonic sensor properties an efficient PC-controlled measuring system has been developed at ifak. In this report this new high performance approach will be presented to make the vibrating ultrasonic sensor surface and also the sound field in front of acoustic sensors in liquids visible.

Vom Modellieren zum Gestalten - Objektorientierung als Impuls für einen neuen Informatikunterricht? - Schulte, Carsten (Informatica Didactica)

Aufgabenbereiche der Medienbildung im Informatikunterricht - Schulte, Carsten; Scheel, Olaf (INFOS)

Possibilistic instance-based learning - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)

Implication-based fuzzy association rules - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)

Instance-based prediction in the framework of possibility theory - Hüllermeier, Eyke; Dubois, D.; Prade, H. (In Proceedings of Workshop on Soft Computing in Case-Based Reasoning, Vancouver, Canada)

Ertragsteuerliche Vorteilhaftigkeitsüberlegungen bei der Verschmelzung einer Kapitalgesellschaft auf eine Personengesellschaft - König, Rolf; Magerkurth, Tanja; Sureth-Sloane, Caren (Steuern und Bilanzen)

BilanzReForm, Steuerbelastungsrechnungen am PC - König, Rolf; Sureth-Sloane, Caren

Implication-based fuzzy association rules - Hüllermeier, Eyke (in Proceedings PKDD-01 5th European Conference on Principles and Practise of Knowledge Discovery in Databases, Freiburg, Germany)

Fuzzy association rules: Semantic issues and quality measures - Hüllermeier, Eyke (in Proceedings of the International Conference on Computational Intelligence 7th Fuzzy Days, Dortmund, Germany)

Toward the representation of implication-based fuzzy rules in terms of crisp rules - Dubois, D.; Hüllermeier, Eyke; Prade, H. (in Proceedings IFSA/NAFIPS-2001 Joint 9th World Congress of the International Fuzzy Systems Association and 20th Internatinonal Conference of the North American Fuzzy Information Processing Society, Vancouver, Canada)

Europäisches Arbeitsrecht - Krimphove, Dieter

Similarity-based inference as evidential reasoning - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Machinelles Lernen und Komplexität - Hüllermeier, Eyke (Ökonomie und Gesellschaft, Jahrbuch 17: Komplexität und Lernen)

Empirische Überprüfung eines synergetischen Konjunkturmodells - Kraft, M.; Hüllermeier, Eyke; Weise, P. (Studien zur Evoltorischen Ökonomik IV)

Strategisches Personalmanagement in globalen Unternehmen

Vom Gründungsmanagement bis zum Neuen Markt

Two-Dimensional Test Data Compression for Scan-Based Deterministic BIST - Liang, Hua-Guo; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

IT-Unterstützung im Customer Relationship Management - Trier, Matthias (Industrie Management Journal)

Dynamically Reconfigurable Processors - Enzler, Rolf; Platzner, Marco

The influence of proportional jitter and delay on end to end delay in differentiated service network - Quynh, Thu Ngo; Karl, Holger; Wolisz, Adam; Rebensburg, Klaus (Network Computing and Applications, 2001. NCA 2001. IEEE International Symposium on)

Circular flow numbers of regular multigraphs - Steffen, Eckhard (J. Graph Theory)

On bicritical snarks - Steffen, Eckhard (Math. Slovaca)

Atomic structure and optical anisotropy of III–V(001) surfaces - Esser, N.; Schmidt, Wolf Gero; Cobet, C.; Fleischer, K.; Shkrebtii, A. I.; Fimland, B. O.; Richter, W. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Structure and Energetics of P-rich GaP(001) Surfaces - Pulci, O.; Schmidt, Wolf Gero; Bechstedt, F. (physica status solidi (a))